Adjustment and adaptation: English curriculum development in pesantren - Dwi Andriani, Zulfi Zumala (Englisia: Journal of Language, Education, and Humanities, 2024)
As the religious institution which focuses on religious teaching, however Pesantren began to incorporate English Language Teaching (ELT) in its curricula by doing some adjustments in line with the Pesantren context. This paper aims to examine English curriculum development at Pesantren Darussalam Blokagung Banyuwangi both in formal and informal institutions inside Pesantren. The incorporation of English Language Teaching (ELT) and the authority of the Pesantren leader in modifying the English curriculum according to the Pesantren context are discussed. The research is a qualitative research approach by employing a case study methodology. The data is collected through in- depth interviews of six participants, observations and documentation. The study reveals two curriculum facets: formal and informal. The formal curriculum aligns with the national school system, while the informal one encompasses English courses progressing from basic to advanced levels, an English language dormitory, and extracurriculars like news reading, storytelling, debate, and public speaking. The research concludes that Pesantren Darussalam effectively integrates English education to complement formal schooling. Yet, to enhance students' English skills and local awareness, ELT materials are needed to be tailored to the Pesantren context. This approach underscores the institution's adaptability and commitment to holistic education.